Incorporation of tailings from the splitting of ornamental rocks in bentonite clay for cosmetic use - Sousa, Antonio Augusto Pereira de; Cordeiro, Maria Barbosa da Silva; Nogueira, Hilda Camila Nascimento; Sousa, Alanna Costa de (Brazilian Journal of Production Engineering, 2021)
Clay masks are identified as the oldest cosmetic preparations used in beauty treatment due to their wide range of properties provided by the minerals present. Thus, it is interesting to study the cosmetic potential of other materials with similar composition, especially those generated in an abundant way and with limited reuse, such as industrial waste. The objective of the present work was to characterize the incorporation of ornamental rocks tailings (RRO) in calcic bentonite clay for use in cosmetology. The adopted methodology consisted of the preparation of two different compositions incorporating the RRO in the calcic bentonite clay, thus, the following analyzes were carried out: pH, moisture content, absolute density, X-ray fluorescence (XRF) and microbiological analysis. The results obtained showed that the composition with the highest amount of bentonite presented more efficient characteristics with regard to cosmetology, that is, lower alkalinity with pH equal to 6 and density content (2,7 g.cm-3) that favors continuous suspension. Both incorporations manifested compliance with microbiological control. When comparing the best incorporation with the commercialized cosmetic clays, based on the chemical composition mostly silico-aluminous, the cosmetic potential of the studied sample is evidenced, since the applicability of clays in the cosmetic area depends primarily on this characteristic.
Keywords: Cosmetics; Industrial sludge; Environmental management; Bentonite; Reuse